Screening as a method of early effective diagnostics of gastric cancer - Domanchuk, Tatyana (Journal of Education, Health and Sport, 2020)
One of the most common forms of malignant neoplasms in the world for more than a decade is gastric cancer. It ranks 2nd in the structure of overall cancer and tends to grow steadily. According to the latest data, the WHO registers 750-850 thousand new cases of gastric cancer every year and more than 600 thousand people die from this disease [1]. Almost the only preventive method today, aimed at early detection of tumors is cancer screening. Its use helps to reduce mortality rate from certain types of malignant neoplasms including gastric cancer. Reasonability to perform screening of the population for malignant neoplasms in Ukraine today remains a matter of debate due to lack of awareness of the population and doctors, lack of clear understanding of the concept and process of screening, complexity and relatively high cost of screening methods, insufficient convincing evidence of its need for certain nosology of malignant tumors [3]. But at the same time, there is an urgent need inUkraine to introduce a gastric cancer screening program to determine its type, as well as to substantiate its reasonability.